Recent Trends in Person Re-Identification: An Overview - et. al., Perni Dedeepya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Person re-identification has significant applications in real time scenarios like forensics and video surveillance. Most of the person re-identification models emphasize on image to image matching or video to video matching as they are easy because of the homogenous matching features. But, in real time applications there will be situations where image is to be matched to a video. This sort of re-identification process is called image to video person re-identification (IVPR), which has significant applications in tracking the location of a lost human and criminal tracking. This method of re-identification has many difficulties due to the heterogeneous matching to be done due to the variation in features of image and video. This article focuses on existing person re-identification methods, their difficulties and further area of research in this field